ANALISIS RANTAI PASOK TANDAN BUAH SEGAR (TBS) PADA PT. SANDABI INDAH LESTARI DI KABUPATEN BENGKULU UTARA - Primalasari, Ira; Sumantri, Bambang; Sriyoto, Sriyoto (Jurnal AGRISEP, 2017)
The objectives of this research were to determine the flow of supply chain Fresh Fruit Bunches in PT. Sandabi Indah Lestari (PT.SIL) and analysis the value of marketing margin earned each marketing agency in the supply chain Fresh Fruit Bunches in PT. SIL. Primary data and secondary data were used in this research which was taken in February 2016 to March 2016. Data collection was done by observation, recording and interviews. Data analysis technique was in this research quantitative descriptive analysis. Based on the results of this research concluded that there were three patterns of flow in the supply chain PT.SIL. The third stream of the supply chain, namely, supply chin flow pattern 1: non plasma farmers - traders - supplier - PT.SIL. The flow pattern of the supply chain II: non plasma farmers - supplier - PT.SIL. The flow pattern of the supply chain III : non plasma farmers – PT. SIL. The flow patterns of supply chain IV: plasma farmers - KSU-BKM - PT. SIL. Marketing margin obtained marketing agencies in the supply chain flow 1 was Rp 230/ kg. Stream supply chain II had a value of marketing margin Rp 230 / kg. The flow of the Supply Chain III had a value of marketing margin 0/Kg. The flow of the supply chain IV had a value of marketing margin of Rp 200 / Kg.